Kepastian Hukum Pemanfaatan Tanah Hak Pengelolaan melalui Perjanjian Sewa Menyewa: Studi di Kawasan Ekonomi Khusus Sei Mangke - Vira Febriyanti; hasim purba; mahmul Siregar (Jurnal Hukum Lex Generalis, 2026)
The construction of lease agreements in the utilization of Management Right (HPL) land at the Sei Mangkei Special Economic Zone by PT KINRA as an extension of PTPN III contradicts Government Regulation Number 18 of 2021, which mandates the use of land transfer and use agreements as the basis for granting Building Use Rights (HGB), Cultivation Rights (HGU), or Use Rights over HPL land. Employing a normative legal method, the findings indicate that lease agreements are not absolutely prohibited under civil law, yet they do not create real rights for investors and cannot serve as the basis for HGB certificate applications. Legal certainty can only be achieved through a deed conforming to GR 18/2021, supported by comprehensive technical guidelines/SOPs and the strengthening of the notary's preventive role. Consequently, aligning the management practices of Right to Manage (HPL) land with statutory provisions serves as a fundamental prerequisite to ensure legal protection for all parties and the sustainability of investments within Special Economic Zones.